2011
DOI: 10.1080/19768354.2011.555119
|View full text |Cite
|
Sign up to set email alerts
|

Vertical nest stratification and breeding success in a six mixed-species heronry in Taeseong, Chungbuk, Korea

Abstract: In 2001, we conducted a study to assess the effects of differential arrival times and nest-site selection on reproductive performance in a mixed-species heronry consisting of six species in Taeseong-ri, Chungbuk, Korea. We recorded the arrival dates, nest heights, clutch sizes, and brood sizes after 15Á20 days of the age of the birds' chicks. The grey herons and cattle egrets arrived first and last, respectively, on the colony site. In the homogenous vegetation structure of the breeding site, the pitch pine tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…On the contrary, grey herons did not show significant differences between breeding years and sites, while the height of the nest tree and nest of great egrets were significantly lower in site B in 2017 than in 2016. Similar to results from a previous study (Park et al 2011), nest tree and nest height of great egrets were lower than those of grey herons, which was probably influenced by the competition for nest sites between these species. Therefore, at site B in 2017, great cormorants selected taller trees for nesting and the height of their nests was higher than in site A in 2016, and the nest and nest tree heights of the grey herons and great egrets seem to have been influenced by the selection of great cormorants.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…On the contrary, grey herons did not show significant differences between breeding years and sites, while the height of the nest tree and nest of great egrets were significantly lower in site B in 2017 than in 2016. Similar to results from a previous study (Park et al 2011), nest tree and nest height of great egrets were lower than those of grey herons, which was probably influenced by the competition for nest sites between these species. Therefore, at site B in 2017, great cormorants selected taller trees for nesting and the height of their nests was higher than in site A in 2016, and the nest and nest tree heights of the grey herons and great egrets seem to have been influenced by the selection of great cormorants.…”
Section: Discussionsupporting
confidence: 87%
“…The heights of the nesting trees at site B were greater than those in site A in both years, while the height of the nests of the great cormorants was greater at site B in 2017 than at site A in 2016. Earlier studies have concluded that the higher the nest tree height, the higher is the breeding success rate (Childress and Bennun 2000;Park et al 2011). Thus, it is possible that the great cormorants moved to areas with taller nest trees.…”
Section: Discussionmentioning
confidence: 99%
“…Equally, nests of the studied species were segregated vertically, which represents another level of habitat partitioning. The vertical separation of nests was observed in the breeding colony of six heron species that nest in pitch pine trees (Pinus rigida): Nycticorax nycticorax, Bubulcus ibis, Egretta alba, Egretta intermedia, Egretta garzetta, and Ardea cinerea (Park et al 2011). The breeding species vertically stratify the nest placements according to their body size, except for Bubulcus ibis and Nycticorax nycticorax, which nest at sites higher than those predicted based on their body size.…”
Section: Discissionmentioning
confidence: 99%